Case Report of Acute Necrotizing Encephalopathy of Childhood Challenge of Diagnostic and Treatment - EL KHETTAB, Fatima zahra; Nde-Ngala, M.; El Khayla, F.; Berramou, I.; Azzouzi, B. El; Merbouh, M.; Serhraoui, H.; Mouaffak, Y.; Jalal, H.; Younouss, S. (International Journal of Innovative Research in Medical Science, 2024)
Acute Necrotizing Encephalopathy of Childhood (ANEC) is a rare disease with a higher prevalence in East Asia. It is characterized by symmetrical and multifocal involvement of areas including the thalamus, brainstem, cerebellum, and white matter. ANEC is associated with death as well as long-term neurological disabilities (sequelae) in individuals who survive. In this report, we describe a case of a child with acute neurological symptoms resulting from a possible infection and explain his brain MRI, and paraclinical symptoms. Introduction: Acute necrotizing encephalopathy of childhood (ANEC) is a progressive encephalopathy. The aim of this study was to report a rare case of ANEC in an eleven-year-old child with bilateral thalamic necrosis. Case Presentation: An 11-year-old child presented four days before admission with an infectious episode characterized by fever (not quantified) and flu-like symptoms. This was further complicated by functional impotence of both lower limbs. MRI showed multiple cerebral lesions above and below the tentorial level, involving the brainstem, cerebellum, thalamus, and bilateral white matter. The patient received intravenous methylprednisolone 30 mg/kg/day and 2 mg/kg for 6 weeks. Discussion: Acute necrotizing encephalopathy of childhood (ANEC) is a rapidly progressing encephalopathy characterized by fever and a depressed level of consciousness. Diagnosis depends on clinical presentation and characteristic neuroimaging findings of abnormal signal flair T2 of the thalami and supratentorial region, followed by treatment with steroids and immunoglobulin, as well as supportive care. Patients with ANEC have a variable prognosis, but mortality is very high. Conclusion: ANEC is a rare neurological entity in children, and its treatment is challenging. Early interventions, including emergency intravenous methylprednisolone or immunoglobulin, or plasma exchange, or a combination of these treatments, are crucial. However, further studies are needed to establish consensus guidelines.